PATIENT EXPECTATIONS FROM AN EMERGENCY MEDICAL SERVICE - Qidwai, Waris; Ali, Syed Sohail; Baqir, Muhammad; Ayub, Semi (Journal of Ayub Medical College Abbottabad, 2005)
Background: Patient expectation survey at the Emergency Medical Services can improve patient satisfaction. A need was established to conduct such a survey in order to recommend its use as a quality improvement tool. Methods: The study was conducted on patients visiting the Emergency Medical Services, Aga Khan University, Karachi. A questionnaire was used to collect information on the demographic profile, and expectations of patients. The ethical requirements for conducting the study were met. Results: A hundred patients were surveyed. The majority was relatively young, married men and women, well educated and better socio-economically placed. The majority of the patients expected a waiting time and a consultation time of less than 30 minutes and 20 minutes, respectively. The majority of respondents expected and agreed to be examined by a trainee but there were reluctant to be examined by the students. There was an expectation that the consultant will examine patients and not advice the attending team over the phone. The majority of the patients expected intravenous fluid therapy. There was a desire to have patient attendant present during the consultation process. The majority of the patients expected to pay less than three thousand rupees for the visit. An expectation exists for investigations and hospitalization. Involvement of patients in decisions concerning their treatment and written feedback on their visit was expected. Conclusions: We have documented the need and value of patient expectation survey at the Emergency Medical Services department. The use of such a tool is recommended in order to improve the satisfaction levels of patients visiting such facilities. Key-words: Emergency Medical Service-Emergency Care-Patient Satisfaction